GENERASI ALPHA: TANTANGAN DAN KESIAPAN GURU BIMBINGAN KONSELING DALAM MENGHADAPINYA - Anwar, Faisal (At-Taujih : Bimbingan dan Konseling Islam, 2022)
The alpha generation is the generation born from 2010-2025. This generation has parents from generations Y and Z. They were born at the same time as the rapid pace of technological development where information technology can be said to be perfect. In contrast to generations Y and Z where information technology technology is still in transition. The alpha generation cannot be separated from gadgets. Their proximity to gadgets has an effect on lifestyle, mindset, way of learning, and even health. This is a concern for many parents. This study aims to describe the character of children who were born as an alpha generation and the readiness of counseling teachers must prepare in dealing with them. The research method in this study is library research with qualitative techniques. The results of a study conducted from several reviewed articles. Guidance and counseling teachers must be creative in providing services to their students. They must also be technology literate in providing services. That's because the children of the alpha generation cannot be separated from gadgets.